1997
DOI: 10.1007/s11746-997-0110-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an antioxidant from fermented soybeans (tempeh)

Abstract: In an exhaustive investigation of the antioxidative properties of tempeh constituents, the substance at R f 0.58 (cyclohexane/ethyl ether, 9:1) was isolated and purified. Until now, only the ultraviolet and fluorescence data of the substance were known, and the presence of an OH group was indicated. In the present paper, the structure of the substance at R f 0.58 was elucidated by the application of spectroscopic methods and found to be 5-(δ-tocopheroxy)-δ-tocopherol. That previous researchers did not confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 7 publications
0
21
0
1
Order By: Relevance
“…[3][4][5] To examine the role of isoflavones in the antioxidant activities of the douchi, isoflavone isomers in the samples during fermentation were determined (Table 1). Neither -glucosides, daidzin, genistin, and glycitin, nor the corresponding aglycone isoflavones, genistein, daidzein, and glycitein changed significantly (p > 0:05) during the 36 h of fermentation, indicating that the Bacillus subtilis used in the present study did not convert glucoside isoflavones to aglycone isoflavones during fermentation.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] To examine the role of isoflavones in the antioxidant activities of the douchi, isoflavone isomers in the samples during fermentation were determined (Table 1). Neither -glucosides, daidzin, genistin, and glycitin, nor the corresponding aglycone isoflavones, genistein, daidzein, and glycitein changed significantly (p > 0:05) during the 36 h of fermentation, indicating that the Bacillus subtilis used in the present study did not convert glucoside isoflavones to aglycone isoflavones during fermentation.…”
Section: )mentioning
confidence: 99%
“…[3][4][5]18) Statistical analysis showed that there was no significant correlation between the changes in aglycone isoflavones and the radical scavenging activity of the douchi during bacterial fermentation (p > 0:05), suggesting that isoflavone contributes little to the changes in the antioxidant activity of douchi.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…11) Free amino acids and oligopeptides in foods have been reported not only to improve the umami taste, but also to have such nutritional advantages as rapid absorption, 12,13) muscle protein maintenance, 13) and antioxygenic activity. 14) These physiological eŠects can also be expected for GABAtempeh, but they do need to be assessed by feeding experiments.…”
mentioning
confidence: 99%
“…The flax plant Linum usitatissimum possesses various tocopherols and carotenoids and some sterols, thus making its oil high in antioxidants. Rapeseed oil and soyabean oil contain high percentage of tocopherols Glycine max L. Amarowicz et al, 1996;Hoppe et al, 1997;Wang, 2002 Coumarins Radical scavenging effect…”
Section: Phototoxicitymentioning
confidence: 99%